Criminal Act of Corruption Abuse of Authority Of Office (Analysis of Decree No.16 Pid.Sus-Tpk/2018/Pn.Jkt.Pst) - Dedi Pulungan; Boy Nurdin; Faisal Santiago (Edunity Kajian Ilmu Sosial dan Pendidikan, 2023)
Corruption in government bodies carried out by bureaucratic machines that are seen is only corruption with a state loss of more than 1 (one) billion, while below one billion is rarely found, because the focus of eradicating corruption is indeed worth 1 billion and above and mostly involves "extraordinary" people. In fact, there are many modes that the ministry is currently preparing when asking the House for a budget. For example, break down a budget package into smaller amounts, but increase the number of packages. This research uses normative juridical legal research methods, namely an approach that includes legal research on legal principles, legal systems, and the level of vertical and horizontal synchronization. Corruption continues to occur, whether in the executive, legislative, or judicial institutions, even among businessmen, all of which are interrelated to facilitate all matters to be achieved. Corruption still occurs and almost every day news of corruption is always published in the news both in print, electronic media and others